(untitled) (Journal of the College of Basic Education, 2020)
The aim of the study is to identify the effect of dual-analysis and Synthesis in problem Solving method for 1st grade students and the sciences material. The sample of the current study was consisted of (60) female students. They were divided in to two groups. Thirty students were as an experimental group and thiry students were as the control group. The experimental group was taught by the strategy of dual analysis and synthesis while the control group was taught by the traditional method. The researcher built a test which consisted of (35) items for seven steps to solve the problems that student faced . After analyzing the results , it has been found that there was a statistically significant difference between the mean score of the students at the level of (0,05) in favour of the experimental group . Finally, the researcher has put down some conclusions, recommendations and suggestions for further research.